INCIDENCE OF '˜Du' IN '˜Rh' NEGATIVE OBSTETRICS PATIENTS - Khan, M. Hussain; Shah, Syed Humayun (Journal of Ayub Medical College Abbottabad, 2000)
Background: A small number of persons with Rh-negative blood have red blood cells that are not directly agglutinated by anti D during routine testing for 'Rh' antigen, but that do react when the D-typing test is converted to the indirect antiglobulin test, which is Du' test. Cells thus identified are then designated as 'Du' cells. This study was done to assess the incidence of '˜Du' patients in Rh negative obstetrics patients. Methods: A total of 1500 pregnant women were screened for Rh antigen. The red blood cells of the D negative subjects were then tested by indirect method. Agglutination confirmed 'Du' otherwise it was confirmed as D (-). Results: Out of the 50 D?negative women subjected to the indirect antiglobulin test 6 women were found to have Du' blood. Conclusions: This reflects a significant percentage of D' negative. Du' subjects in our obstetrics patients. Therefore, utmost care should be taken before labeling a subject D' negative.